Writing Self-Efficacy in English Language Learning: A Study of University Students' Academic Achievement and Motivational Factors - Ariyanti (Borneo Educational Journal (Borju), 2025)
This study examines the relationship between writing self-efficacy and academic performance among university students enrolled in English writing courses. Using a mixed-methods approach, data were collected from 150 university students across three institutions in East Java, Indonesia. The study employed the Questionnaire of English Writing Self-Efficacy (QEWSE) and semi-structured interviews to assess students' self-efficacy beliefs and identify influencing factors. Results revealed a significant positive correlation between writing self-efficacy and academic performance (r = .67, p < .001). Key predictors of writing self-efficacy included previous English learning experience (β = .34, p < .001), quality of instructor feedback (β = .28, p < .001), peer collaboration opportunities (β = .22, p < .01), and perceived task difficulty (β = -.19, p < .05). Qualitative findings highlighted five major themes: mastery experiences, instructor feedback quality, peer support, task relevance, and technological resources. The study provides empirical evidence for the importance of writing self-efficacy in L2 contexts and offers practical implications for English language pedagogy in higher education. The findings highlight actionable strategies for improving English writing instruction, including the role of peer support, feedback mechanisms, and task design, particularly in EFL university settings.